Impact of moisture on efficiency-determining electronic processes in perovskite solar cells. Issue 22 (26th May 2017) - Salado, Manuel; Contreras-Bernal, Lidia; Caliò, Laura; Todinova, Anna; López-Santos, Carmen; Ahmad, Shahzada; Borras, Ana; Idígoras, Jesús; Anta, Juan A.
Abstract : Moisture-induced degradation in perovskite solar cells was thoroughly investigated by structural (SEM, EDS, XRD and XPS) and device characterization (impedance and intensity modulated photocurrent spectroscopy) techniques. Abstract : Moisture-induced degradation in perovskite solar cells was thoroughly investigated by structural (SEM, EDS, XRD and XPS) and device characterization (impedance and intensity modulated photocurrent spectroscopy) techniques. Both the influence of the perovskite composition and the nature of the hole selective material were analyzed. The degradation rate was found to be significantly slower for mixed perovskites and P3HT-based devices. However, for a fixed degradation degree (defined as a 50% drop from the initial photocurrent), all configurations show similar features in small-perturbation analysis. Thus, a new mid-frequency signal appears in the impedance response, which seems to be related to charge accumulation at the interfaces. In addition, faster recombination, with a more important surface contribution, and slower transport were clearly inferred from our results. Both features can be associated with the deterioration of the contacts and the formation of a higher number of grain boundaries.